E-modul Pendidikan Pancasila Berbasis Canva Berbantuan Flip PDF Profesional untuk Meningkatkan Hasil Belajar Siswa Sekolah Dasar - Ramadhan, Wandri; Meisya, Rovika; Jannah, Raudhatul; Putro, Khamim Zarkasih (University of Muhammadiyah Malang, 2023)
This study identifies the limitations of conventional teaching methods, such as textbooks and lectures, in delivering Pancasila education to fourth-grade elementary school students. These methods could be more engaging and effective in improving students' learning outcomes and understanding of the subject matter. This research aims to develop an interactive and engaging E-module to enhance students' learning outcomes and understanding of Pancasila values. This research employed a developmental approach known as Randomized Controlled Trial (RCT) using the 4D model (Define, Design, Develop, and Disseminate). The validity of the E-module is assessed through expert validation involving media and subject matter experts. The evaluation results demonstrate the high validity of the developed Pancasila Education E-module, created using Canva for Education and assisted by Flip PDF Professional. The Aiken V index indicates a score of 0.87%, with all evaluation aspects falling within the 0.8 ≤ V ≤ 1 range. Moreover, the practicality of the E-module is confirmed, with a practicality level of 84.3%. The E-module was tested by teachers and fourth-grade students, with the involvement of the entire class. The test results show an improvement in students' learning outcomes, with an overall pretest percentage of 95.5% and a post-test percentage of 92.5%. Hence, the Pancasila Education E-module effectively enhances students' learning outcomes and understanding of Pancasila values. This research enriches the teaching methods of Pancasila education in fourth-grade elementary schools.